Decreasing loneliness and social isolation among the older people: systematic search and narrative review (Epidemiology, Biostatistics, and Public Health, 2022)
IntroductionThe aim of this study is to sum up the current knowledge on the effectiveness of the existing interventions for alleviating loneliness and social isolation among elderly persons.MethodsWe used a systematic approach and performed a literature search of MEDLINE, ISI Web of science, SCOPUS, The Cochrane Library, and CINAHL databases. After identifying 13 eligible reviews addressing interventions of our interest, we proceeded with a narrative description of the study findings.ResultsThe initiatives largely encompassed one-to-one interventions, group activities or community engagement approaches. In particular, technology interventions were recently given much attention. Overall, the studies showed non-satisfying methodological quality and their results were often inconclusive.ConclusionsAlthough there is a growing body of evidence referring to implementation of interventions targeting social isolation and loneliness among the elderly, future well-designed interventions are necessary in order to draw firm conclusions.